Leishmania major telomerase RNA knockout: From altered cell proliferation to decreased parasite infectivity - de Oliveira, Beatriz Cristina Dias [UNESP]; Shiburah, Mark Ewusi [UNESP]; Assis, Luiz Henrique Castro [UNESP]; Fontes, Veronica Silva [UNESP]; Bisetegn, Habtye [UNESP]; Passos, Arthur de Oliveira [UNESP]; de Oliveira, Leilane S. [UNESP]; Alves, Cristiane de Santis; Ernst, Evan; Martienssen, Rob; Gallo-Francisco, Pedro Henrique; Giorgio, Selma; et al. (Elsevier, 2024)
This study focuses on the biological impacts of deleting the telomerase RNA from Leishmania major (LeishTER), a parasite responsible for causing leishmaniases, for which no effective treatment or prevention is available. TER is a critical player in the telomerase ribonucleoprotein complex, containing the template sequence copied by the reverse transcriptase component during telomere elongation. The success of knocking out both LeishTER alleles was confirmed, and no off-targets were detected. LmTER−/− cells share similar characteristics with other TER-depleted eukaryotes, such as altered growth patterns and partial G0/G1 cell cycle arrest in early passages, telomere shortening, and elevated TERRA expression. They also exhibit increased γH2A phosphorylation, suggesting that the loss of LeishTER induces DNA damage signaling. Moreover, pro-survival autophagic signals and mitochondrion alterations were shown without any detectable plasma membrane modifications. LmTER−/− retained the ability to transform into metacyclics, but their infectivity capacity was compromised. Furthermore, the overexpression of LeishTER was also deleterious, inducing a dominant negative effect that led to telomere shortening and growth impairments. These findings highlight TER's vital role in parasite homeostasis, opening discussions about its potential as a drug target candidate against Leishmania.
Keywords: Altered cell proliferation; Decreased infectivity capacity; Leishmania spp.; Telomerase RNA knockout and overexpression; Telomere shortening; TERRA upregulation